Transition-metal dichalcogenides for spintronic applications - Zibouche, Nourdine; Kuc, Agnieszka; Musfeldt, Janice; Heine, Thomas (Annalen Der Physik, 2014)
Spin-orbit splitting in transition-metal dichalcogenide monolayers is investigated on the basis of density-functional theory within explicit two-dimensional periodic boundary conditions. The spin-orbit splitting reaches few hundred meV and increases with the size of the metal and chalcogen atoms, resulting in nearly 500 meV for WTe2. Furthermore, we find that similar to the band gap, spin-orbit splitting changes drastically under tensile strain. In centrosymmetric transition metal dichalcogenide bilayers, spin-orbit splitting is suppressed by the inversion symmetry. However, it could be induced if the inversion symmetry is explicitly broken, e.g. by a potential gradient normal to the plane, as it is present in heterobilayers (Rashbasplitting). In such systems, the spin-orbit splitting could be as large as for the heavier monolayer that forms heterobilayer. These properties of transition metal dichalcogenide materials suggest them for potential applications in opto-, spin- and straintronics.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Density-functional theory; Monolayers; Spin-orbit coupling; Transition-metal dichalcogenides